Fish biodiversity at Pulau Tuba and Kilim Geopark, Langkawi, Malaysia - Mohd Sairi, Mohamad Najmuddin; Ahmad Kamil, Khairunnisa; Tajam, Jamil (Faculty of Applied Sciences, 2025)
The continuous development of tourism, fishing and other activities in Langkawi, Malaysia have increasingly pressured the island’s marine ecosystem. Monitoring the impacts is crucial for ensuring the sustainable development of the area. Fish population dynamics are widely used as an ecological indicator for assessing pollution levels and overall health of aquatic ecosystems. The objective of this research is to assess the biodiversity (richness and evenness) of fish species at Pulau Tuba and Kilim GeoPark as to evaluate the impacts of surrounding activities. This research was conducted at two locations within the waters surrounding Pulau Langkawi: Pulau Tuba and Kilim GeoPark, which were selected due to their similar coastal topology and characteristics but varying level of anthropogenic activities. The fish sampling was carried out three times at three different points in each study area. The data were analyzed using Shannon-Wiener and Simpson’s diversity indices to determine the significant differences in fish species diversity between the two locations. Fish biodiversity index at Pulau Tuba was recorded at 1.52 while Kilim GeoPark was 1.32. The results indicated that the biodiversity of fishes found at Pulau Tuba is higher although it is not significantly different than at Kilim GeoPark. These suggest that anthropogenic activities may have given an impact toward the biodiversity of fish, but more data is needed to confirm the hypothesis. A continuous and more rigorous monitoring is suggested to have a more comprehensive input for policy design. The impact of surrounding activities may take some time to affect the fish dynamics, thus more direct impact such as water quality shall be recommending for future studies.